Caffeine Attenuates Electroacupuncture Effect on Pressure Pain Threshold and Tolerance in Healthy Individuals: A Randomized Controlled Trial - Liu, Kun; Cui, Xiang; Zhi, Mujun; Zhang, Meng; Zhao, Ting; Gao, Xinyan; Zhu, Bing (Frontiers in Neurology, 2022)
Introduction The effect of caffeine on acupuncture analgesia in humans is unclear. This study aimed to investigate whether caffeine-containing beverage intake influences the effect of electroacupuncture (EA) on static quantitative sensory testing (QST) and dynamic QST in healthy subjects. Methods A total of 40 healthy subjects were enrolled and randomly assigned to receive coffee containing moderate doses of caffeine (coffee group) or non-caffeinated juice (juice group) for 4 weeks. The primary outcome measures were the pressure pain threshold (PPT), pressure pain tolerance (PPTo), and heat pain threshold (HPT) as static QST parameters. Numerical rating scales (NRS) of heat stimulus and nociceptive flexor reflex (RIII reflex), as parameters of dynamic QST, were also examined. EA stimulation with tolerance intensity was performed at ST36 (Zusanli)-GB34 (Yanglingquan) points at weeks 0, 2, and 4. PPT, PPTo, and HPT were detected pre- and post- EA. The NRS scores were examined pre-, during, and post-EA, and 1 min after EA was completed. The RIII reflex was examined pre- and 1–5 min post-EA. Results At week 0, both groups showed increased PPT and PPTo and decreased NRS scores of heat stimuli and RIII reflex after EA, but HPT was not affected. After 4 weeks, the effects of EA on PPT and PPTo were attenuated in the coffee group compared to the juice group, whereas the effect of EA on the NRS scores and RIII reflex were not influenced. There was no significant difference found at week 2 for these indications. EA also did not affect the HPT in both groups at week 4. Conclusion Moderate caffeine intake reduced the effects of EA on PPT and PPTo in healthy subjects.